Lizards as sentinels for the distribution of Angiostrongylus cantonensis - Anettová, Lucia; Baláž, Vojtech; Coufal, Radovan; Horsák, Michal; Izquierdo-Rodriguez, Elena; Šipková, Anna; Foronda, Pilar; Modrý, David (Epidemiology and infection, 2024)
The rat lungworm Angiostrongylus cantonensis is a zoonotic metastrongyloid nematode currently considered an emerging pathogen. Originating in Southeast Asia, this nematode has spread to tropical and subtropical parts of the world via its invasive rodent and gastropod hosts.On the island of Tenerife in the Canary archipelago, the A. cantonensis invasion was recognized more than a decade ago. The endemic lizard Gallotia galloti has been identified as a paratenic host of this nematode in the Canary Island ecosystem. Because this lizard species is the most abundant reptile in Tenerife, we tested its suitability as a possible sentinel for A. cantonensis presence. Lizards were captured alive in nine localities, spanning an environmental gradient across the island. Tail muscle tissue was obtained by provoked caudal autotomy and tested for the nematode infection by a species-specific qPCR. Infection intensities were assessed by detecting A. cantonensis DNA quantities based on a calibrated standard curve. Of the 129 samples tested, 31 were positive. The prevalence varied among localities, with the highest (63.6%) recorded in a humid laurel forest. Even though the prevalence in Valle San Lorenzo was the lowest, this is the first record of A. cantonensis from the arid south of Tenerife. Variation in prevalence at different localities was significantly and positively correlated with increasing vegetation cover and negatively correlated with seasonal variability of precipitation, as determined by Spearman correlation coefficients. Fisher's exact test was used to determine the variation in the prevalence of A. cantonensis among adult males, females, and juveniles and showed no significant difference. Also, there was no significant difference in infection intensity between males and females (as determined by GEE-g). We demonstrated that provoking caudal autotomy can be an effective non-lethal method of A. cantonensis mapping in island ecosystems with abundant lizard species, particularly those with a sharp climatic and vegetation gradient, from xeric to humid conditions.
Keywords: Male; Spain; Strongylida Infections; sentinels; prevalence; mužské pohlaví; infekce hlísticemi řádu Strongylida; Lizards; caudal autotomy; ještěři; Sentinel Species; sentinelové organismy; Animals; rat lungworm; ženské pohlaví; Španělsko; zvířata; Prevalence; lizards; Female; Angiostrongylus cantonensis